Structural and electronic properties of potassium-doped 1, 2;8, 9-dibenzopentacene superconductor: comparing with doped [7]phenacenes. (16th February 2017) - Zhong, Guo-Hua; Zhang, Chao; Yan, Xunwang; Li, Xiaoguang; Du, Zheng; Jing, Gexin; Ma, Cencen
ABSTRACT: Polycyclic aromatic hydrocarbons doped by metal have exhibited the potential of high temperature superconductivity. Understanding the basic properties of materials is the key to reveal the superconductivity. Here, a systemically theoretical study has been done to explore crystal structures and electronic properties of pristine and potassium-doped 1, 2;8, 9-dibenzopentacene, compared with [7]phenacenes case. We determined that vdW-DF2 functional is more suitable to describe the non-local interaction in a molecular crystal. Based on this functional, we predicted the crystal structures and investigated in detail the K atomic positions in a system. It was found that the intralayer doping leads to lower total energy. From the calculated formation energy, for each 1, 2;8, 9-dibenzopentacene molecule, the doping of two electrons is more stable under the relatively K-poor condition while the doping of four electrons is more stable under the K-rich condition. Between these two phases, the three-electron doping phase stabilises in a narrow region of K chemical potential. Combining with the electronic states at Fermi level, we analysed the reasons of superconductivity enhancement in doped 1, 2;8, 9-dibenzopentacene. This work further deepens the understanding of 1, 2;8, 9-dibenzopentacene superconductor. GRAPHICAL ABSTRACT: